2010
DOI: 10.1021/jp907870a
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Synthesis and Electrical Behavior of Nanometric β-NiMoO4

Abstract: Metallic molybdates are of great importance for their potential use as catalysts of selective nature. The synthesis of the β-NiMoO4 phase is not simple and has been approached employing different methods; however, combustion synthesis has never been proposed before. This work describes the synthesis of nanometric β-NiMoO4 powders from mixtures of Ni (II) and Mo (VI) acetylacetonates as cation precursors and urea as fuel. The characterization of the as-prepared combustion product showed that the combustion synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
69
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 23 publications
4
69
0
Order By: Relevance
“…Metal molybdates are important ternary oxide ceramics with unique chemical and physical properties [1][2][3][4][5][6][7] that enable their use as catalysts for the catalytic oxidative dehydrogenation (ODH) of light alkanes to their corresponding olefins [8][9][10][11][12][13]. Nickel molybdate (NiMoO 4 ) is the most active and selective catalyst of these for converting propane to propylene [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Metal molybdates are important ternary oxide ceramics with unique chemical and physical properties [1][2][3][4][5][6][7] that enable their use as catalysts for the catalytic oxidative dehydrogenation (ODH) of light alkanes to their corresponding olefins [8][9][10][11][12][13]. Nickel molybdate (NiMoO 4 ) is the most active and selective catalyst of these for converting propane to propylene [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Two phases (a and b) usually exist at atmospheric pressure, which are both monoclinic but exhibit different Mo coordination, i.e., of octahedral and tetrahedral sites, respectively [15][16][17][18][19][20][21][22][23]. The a phase is stable at room temperature, whereas the b phase starts to crystallize between 550 and 670 C. The electrochemical properties of the materials are closely dependent on their crystal structures and morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…The a phase is stable at room temperature, whereas the b phase starts to crystallize between 550 and 670 C. The electrochemical properties of the materials are closely dependent on their crystal structures and morphologies. However, there have only been a few studies on a and b phase mixtures for LIB anode materials because of the difficulties involved in preparing the pure b phase [23][24][25]. For example, Haetge et al [15] prepared nanocrystalline a/b-NiMoO 4 thin film anodes with 3D honeycomb structures using polymer templates, and Park et al [18] suggested a/b-NiMoO 4 with a nanowire structure for the anode material.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the synthesis, characterization, and properties of nanoscale metal molybdates and tungstates, however, have comparably limited to date. Most often nanoscale molybdates and tungstates have been gained via simple water-based precipitation, [ 3 ] freeze-drying, [ 8 ] hydrothermal/solvothermal reactions, [ 9 ] thermal combustion, [ 10 ] or mechanochemical treatment. [ 11 ] Quite often the described materials were obtained with comparably large diameter (i.e., greater than 80 nm), and broad size distribution.…”
Section: Introductionmentioning
confidence: 99%